State Regulations and Religious Endowments (Awqaf): Evaluating the Impact of the Waqf Amendment Bill 2025 on Minority Rights - Hassan, Imza; Dar, Showkat Hussain (PT. Riset Press International, 2026)
The management of religious endowments, or Awqaf, has long been a sensitive intersection of state authority and minority rights in India. The Waqf Amendment Bill 2025 represents a significant legislative shift, introducing fundamental changes to how Waqf properties are identified, registered, and administered. This research evaluates the socio-legal implications of the Bill, focusing on the expanded role of the state in supervising religious assets and the potential dilution of the